Biodegradation characteristics and size fractionation of landfill leachate for integrated membrane treatment - Insel, Guclu; Dagdar, Mina; Dogruel, Serdar; Dizge, Nadir; Cokgor, Emine Ubay; Keskinler, Bülent (Elsevier, 2013)
The fate of organics and nitrogen during the biological treatment with MBR and subsequent membrane filtration processes (nano filtration, NE; reverse osmosis, RO) were investigated for a landfill leachate. The chemical oxygen demand (COD) and total Kjeldahl nitrogen (TKN) removal performances of membrane bioreactor (MBR) were obtained to be around 89% and 85%, respectively. The effluent COD of MBR was measured to be 1935 mg/L (30 kDa) which is much lower than experimentally determined soluble inert COD of 3200 mg/L using 0.45 mu m filter. The readily and slowly biodegradable COD fractions were estimated to be 17% and 52% of raw influent COD, respectively. The respirometry based modeling test performed on raw leachate exhibited much slower degradation kinetics compared to municipal wastewater. A unique subset of model parameters was extracted from batch respirometry by using acclimated MBR sludge. The sequential ultrafiltration (UF) experiments (particle size distribution, PSD) revealed that most of the organics was below 2 nm filter mesh size. In addition, NF/RO post treatment after MBR system was required to increase COD and total nitrogen (TN) removal performances up to 99%. Relatively lower salt rejection rates around 94% was obtained for RO system as a post treatment of MBR system. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: COD fractionation; Particle size distribution; Respirometry; MBR; Nanofiltration; Reverse osmosis